2011
DOI: 10.1116/1.3664122
|View full text |Cite
|
Sign up to set email alerts
|

Growth and electrical properties of silicon oxide grown by atomic layer deposition using Bis(ethyl-methyl-amino)silane and ozone

Abstract: Silicon oxide thin film grown at low temperatures (<300–500 °C) is essential for a range of applications in semiconductor devices. In this study, silicon oxide films were deposited at a substrate temperature of ∼300 °C by an atomic layer deposition (ALD) process using Bis(ethyl-methyl-amino)silane (BEMAS). BEMAS precursors adsorbed on the growing surface reacted with ozone but not with H2O. This suggests that the Si–H bonds in the BEMAS precursors adsorbed on the surface are robust and could be cleaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…[ 65 ] Although chlorosilanes (e.g., SiCl 4 , SiH 2 Cl 2 and Si 2 Cl 6 ) are currently used for ALD of silicon nitride with NH 3 or N 2 as nitrogen source, [57][58][59]66,67 ] a chlorine-free low-temperature CVD or, ideally, ALD process would be preferred for many applications. Finding alternative Si precursors, and optimizing existing families such as aminosilanes, is therefore the motivation for some of the theoretical work presented here and for ongoing research.…”
Section: Modeling the Ald Of Silicon-based Materialsmentioning
confidence: 99%
“…[ 65 ] Although chlorosilanes (e.g., SiCl 4 , SiH 2 Cl 2 and Si 2 Cl 6 ) are currently used for ALD of silicon nitride with NH 3 or N 2 as nitrogen source, [57][58][59]66,67 ] a chlorine-free low-temperature CVD or, ideally, ALD process would be preferred for many applications. Finding alternative Si precursors, and optimizing existing families such as aminosilanes, is therefore the motivation for some of the theoretical work presented here and for ongoing research.…”
Section: Modeling the Ald Of Silicon-based Materialsmentioning
confidence: 99%
“…Similarly, through the introduction of an amino group, aminosilane precursors play an important role of self-catalysing in Si-O formation of SiO 2 ALD. 12,25 Recently, various alkylaminosilane-based molecules with appropriately reactive functional ligands have been evaluated and tested with the aim to identify most suitable precursors for SiO 2 thin lm growth both experimentally [26][27][28][29][30][31][32] and theoretically. [15][16][17][33][34][35] It was found that an increase in the degree of alkylamino substitution on Si atom would result in a reduced deposition rate and a use of tris(alkylamino)silane-based precursors may lead to a higher degree of impurity in the lms, especially in a low temperature range of the ALD window.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a shows a conventional X-TEM image of a 20 nm pitch DRAM gBC pattern after Si gap-filling and etching back (including additional thermal nitride deposition and etching-back). Though the amino-silane was used for uniform nucleation before thermal CVD growth [1], there were large voids near the interface between the active Si and the thermal grown Si, because Si was simultaneously grown from the bottom active Si and the side wall dielectric. The TEM image also shows that the thermal grown amorphous Si at the contact area was crystallized, thus forming the CEG due to the thermal process (~800 °C) of the following nitride deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The main reasons for this limitation are seam and void formation near the middle of the contact area, which results from higher doping concentrations. Numerous alternative solutions for these difficulties have been proposed, such as thermal CVD with an amino-silane seed layer [1], Si implantation after Si etch-back, flowable CVD and laser-induced epitaxial growth [2]. However, all of these methods cannot meet simultaneously requirements.…”
Section: Introductionmentioning
confidence: 99%